Novel Gyroviruses, including Chicken Anaemia Virus, in Clinical and Chicken Samples from South Africa - Smuts, Heidi E. M. (Hindawi Publishing Corporation, 2014)
Introduction. Chicken anaemia virus, CAV, was until recently the only member of the Gyrovirus genus. 6 novel gyroviruses, AGV2, HGyV1, and GyV3-6, have since been discovered in human and chicken samples. Methods. PCR amplification of the VP2 gene was used to detect AGV2/HGyV1, GyV3, and CAV in a range of clinical samples including stool, respiratory, CSF, and HIV-positive plasma. Screening of fresh local chicken meat was also performed. Results. AGV2/HGyV1 or GyV3 was detected in stools from healthy children (17/49, 34.7%) and patients with diarrhoea (22/149, 14.8%). 1.2% (3/246) nasopharyngeal respiratory samples were positive. No AGV2/HGyV1 or GyV3 was detected in nasal swabs from wheezing patients, in CSF from patients with meningitis, and in HIVpositive plasma. CAV was found in 51% (25/49) of stools from healthy children and 16% (24/149) in diarrhoea samples. Screening of 28 chicken samples showed a higher prevalence of gyrovirus (20/28, 71%) compared to CAV (1/28, 3.6%). Phylogenetic analysis of the CAV VP1 gene showed South African sequences clustering with Brazilian isolates from genotypes D2 and A2. Conclusion. Novel gyroviruses, including CAV, are present in the South African population with diarrhoea and respiratory illness as well as in healthy children. Their presence suggests an origin from chicken meat consumption.